Natural disasters and economic inequality: Insights from wildfires across the globe - Jayash Paudel (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
Natural disasters cause economic damages and may exacerbate disparities in income distribution among countries across the globe. This article employs satellite data on real-time active fire locations to evaluate the short-term impact of forest fires on economic inequality around the world. Using quasi-random spatial and temporal variation in both the incidence and intensity of fire events, the study employs year and country fixed effects to show that wildfires exacerbate economic inequality among rural areas. Results indicate that the Gini index in rural areas increases by 13.72 per cent and 22.02 per cent for every additional unit increase in the number of wildfires (incidence) and fire radiative power (intensity), respectively. As the number of fire events increases, the impact of fire radiative power on economic inequality is less negative, implying that natural disasters may serve as a means of creative destruction. This effect is prominent among uppermiddle-income countries and those belonging to East Asia and the Pacific region. These findings contribute to a better understanding of the economic cost of natural disasters and offer policy implications for achieving sustainable development goals.
Keywords: D62; R40; R41; R48; 330; natural disasters; wildfires; Gini index; inequality; income